(untitled) (Al-Mansour Journal, 2022)
In the light of the rapid shift towards the knowledge economy, the knowledge and cognitive skills one of factors of production job, so the volume of investment spending by business units and business organizations to invest in the knowledge and the formation of these skills, but in fact there is no method or technique which you can measure the size of the expected benefits of this investment, so the aim of the research was an attempt to establish the foundations and the criteria currently used to measure the productivity of knowledge work and put a suitable replacement from the standpoint of a researcher in measuring this variable at the level of economic units with high knowledge content.